In vitro Survival of Follicles Collected from Domestic Cats' Ovaries at Different Stages of Oestrous Cycle and Cultured with IGF-1 - Alves, E. A. [UNESP]; Padilha, L.; Savi, P. A.; Apparicio, M. F.; Mostachio, G. Q.; Motheo, T. F.; Pires-Buttler, E. A.; Vicente, W. R. R.; Luvoni, G. C. (Wiley-Blackwell, 2012)
Contents Optimal conditions for in vitro culture of feline ovarian follicles have not yet been defined. Follicular development is regulated by intraovarian growth factors, as insulin-like growth factor (IGF-1), and during the different stages of the oestrous cycle, follicles are exposed to specific hormonal environments. The aim of this study was to investigate the effect of IGF-1 on in vitro growth and granulosa cell (GC) viability of preantral follicles collected from domestic cats at follicular and luteal phases of the oestrous cycle. Oestrus and ovulation were induced in 12 cats. A total of 39 and 32 follicles collected at the follicular and luteal phases, respectively, were individually cultured in vitro for 6 days in minimum essential medium media supplemented with or without IGF-1 (100 ng/ml). Follicles collected during the follicular phase and cultured without IGF-1 displayed a significant increase in size and higher GC viability (46.5 +/- 22.1 mu m, 66.7%, respectively) than that of follicles collected at the luteal phase and cultured without IGF-1 (26.7 +/- 14.4 mu m, 50%, respectively; p < 0.05). In contrast, when IGF-1 was added to the culture medium, no differences were observed in size or GC viability between follicles collected at the two phases of the cycle. Nonetheless, follicles collected at the luteal phase and cultured with IGF-1 had a significant increase in their diameter and GC viability (31.9 +/- 15.9 mu m, 63.6%, respectively) than that cultured without IGF-1 (26.7 +/- 14.4 mu m, 50%, respectively; p < 0.05). These data suggest that in vitro growth and GC survival of feline preantral follicles are affected by the oestrous cycle phase, and the IGF-1 exerts a positive effect on follicles collected at the luteal phase.